OUTCOMES OF PATIENTS ON VENTILATORY SUPPORT IN CORONARY CARE UNIT; A STUDY AT AFIC - Siddiqui, Abdul Hamid; Khan, Muhammad Qaiser; Abbas, Safder; Naqvi, Shahab; Aziz, Sohail; Shahram, Syed (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the outcome of patients and determine prognostic factors associated with death in patients on mechanical ventilation in coronary care unit.Study Design: Descriptive cross sectional study.Place and Duration of Study: Study was conducted at AFIC/NIHD Rawalpindi from Jan 2012 to Dec 2012.Materials and Methods: A total of 104 consecutive patients who underwent endotracheal intubation and mechanical ventilation admitted to coronary care unit of AFIC-NIHD form January 2012 to December 2012.Results: The following criteria were higher for non survivors: Acute physiology and Chronic Health Evaluation (APACHI) II score 15 ± 4.8 vs 10 ± 5 (p < .0001), lower arterial PH7.25 ± .08 vs 7.33 ± .09 (p 15 (95% confidence interval 0.747-1.071), Mean arterial pressure < 45 mmHg (95% confidence interval 1.058-1.308) and lower arterial PH < 7.25 (95% confidence interval .209-.480).Conclusion: Higher mortality in coronary care unit in patients on ventilatory support is multi-factorial in origin but a few parameters like mean arterial pressure, APACHI score and arterial PH are better predictors of adverse outcome and may reflect the severity of underlying ischemic heart disease. Particular attention towards adverse outcome predictors, reduction of coronary ischaemia, co-morbids, and control of infection and use of standardized weaning protocol may improve dismal outcome of these patients.